Approaching an efficient means of addressing urban environmental challenges: a review of Ghana's "reactive" measures to "proactive" measures. Issue 11 (2nd November 2021) - Amponsah, Ebenezer Impriam
ABSTRACT: Urban development has been one of the advanced world's most significant characteristics. Within many parts of the world, economic growth, technological innovations, and socio-cultural change are visible attributes. Nonetheless, Ghana and many countries in Sub-Saharan Africa has been faced with limitations rendering cities and urban areas incapable to perform effectively in the national development agenda. Measures implemented to achieve proper urban planning and sustainability are considered to be those that can offer long-lasting solution and balance environmental benefits with socioeconomic growth. All things being equal, there is an expectation of little or no flaws for urban sustainability, yet findings from previous studies indicate recurring environmental challenges in urban Ghana with a hike in the depletion of natural resources. This paper evaluates the efficiency of the "reactive" measures used to tackle urban environmental challenges in Ghana and advocates for the adoption of "proactive" measures after a meticulous review of literature. With the study findings suggesting inefficiencies and unsuitability in the "reactive" measures, the end goal is for the building of stronger institutions and enhancing environmental governance for better urban growth in Ghana.